Ultra-light and ultra-thin aluminum foil material for energy storage and preparation method thereof

By optimizing the alloy composition and processing technology, ultra-thin aluminum foil with a thickness in the range of 5 to 10 μm was prepared, which solved the problem of difficult to take into account both material strength and conductive properties in the prior art, and achieved efficient preparation of ultra-thin aluminum foil materials, significantly improving the energy density and service life of energy storage equipment.

CN119776701APending Publication Date: 2025-04-08INNER MONGOLIA LIANSHENG NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411723468.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing ultra-light and thin aluminum foil materials are difficult to maintain mechanical strength and conductivity during the preparation process, and are prone to defects during the processing process, resulting in stability and reliability problems. At the same time, the preparation process is high and the efficiency is low.

Method used

By optimizing the alloy composition and processing technology, ultra-thin aluminum foil with a thickness in the range of 5 to 10 μm was prepared. The rapid cooling and multi-pass cold rolling process were used to maintain the mechanical strength and conductivity, and a uniform oxide film was formed through surface chemical oxidation treatment to improve corrosion resistance.

Benefits of technology

The mechanical strength and conductivity of ultra-light and thin aluminum foil material are achieved, which significantly reduces the weight of energy storage equipment, improves energy density and specific energy, and at the same time extends the service life of the material and enhances its adhesion to the electrode active material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an ultrathin aluminum foil material for energy storage and a preparation method thereof, the alloy components of the aluminum foil material comprise Al, 0.2%-0.5% of Mn, 0.1%-0.3% of Mg and 0.1%-0.2% of Si, the thickness of the aluminum foil is 5-10 [mu] m, and the surface of the aluminum foil is coated with an oxidation film with the thickness of 20-50 nm. The material has excellent mechanical properties, conductivity and corrosion resistance. The preparation method comprises the steps of smelting and casting, hot rolling, cold rolling, heat treatment, surface treatment, finished product processing and the like, the smelting temperature, the cold rolling compression ratio, the annealing process and surface oxidation treatment parameters are optimized in detail, and the comprehensive performance of the aluminum foil is remarkably improved. Compared with the prior art, the ultrathin aluminum foil is realized, the mechanical strength and the conductivity are both considered, and the corrosion resistance is improved. The prepared aluminum foil material is suitable for energy storage devices such as lithium ion batteries and supercapacitors, meets the requirements for high energy density and light weight, and has excellent industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of aluminum foil materials, and more specifically to an ultra-light and thin aluminum foil material for energy storage and a preparation method thereof. Background Art

[0002] At present, the development and utilization of new energy sources are increasingly becoming the focus of global attention. As an important part of the new energy field, energy storage technology is of great significance for improving energy utilization efficiency and ensuring the stability of energy supply. Among them, aluminum foil, as one of the core materials of energy storage equipment, is widely used in lithium-ion batteries, supercapacitors and other energy storage devices due to its excellent electrical conductivity, thermal conductivity, mechanical strength and processability.

[0003] Traditional aluminum foil materials for energy storage are usually thick and heavy, which makes it difficult to meet the requirements of modern energy storage devices for lightweight, thin and high performance. As energy storage devices develop towards high energy density and high efficiency, ultra-thin aluminum foil materials have gradually become a research hotspot. The application of thin aluminum foil can not only significantly reduce the weight of energy storage devices, but also effectively improve the volume energy density and specific energy of energy storage devices.

[0004] However, the preparation of ultra-thin aluminum foil materials still faces many technical challenges. First, while traditional processes can achieve ultra-thin aluminum foil, they can easily lead to a decrease in the mechanical strength and electrical conductivity of the material, making it difficult to meet the needs of actual applications. Secondly, ultra-thin aluminum foil is prone to defects during processing, such as pinholes and cracks, which will directly affect its stability and reliability in energy storage devices. In addition, the high cost and low efficiency of the preparation process also restrict the large-scale promotion and application of ultra-thin aluminum foil materials. Summary of the invention

[0005] In order to solve the shortcomings of the prior art, an ultra-light and thin aluminum foil material for energy storage and a preparation method thereof are provided. The specific scheme is as follows:

[0006] An ultra-light and thin aluminum foil material for energy storage, wherein the alloy component of the aluminum foil material includes Al;

[0007] Mn 0.2% to 0.5%; Mg 0.1 to 0.3%; Si 0.1 to 0.2%; the thickness of the aluminum foil is 5 to 10 μm; the surface of the aluminum foil is coated with an oxide film, and the thickness of the oxide film is 20 to 50 nm.

[0008] Furthermore, the preparation method comprises the following steps:

[0009] S1. Melting and casting: Put high-purity aluminum and trace alloy elements into a melting furnace according to the proportion, and add alloy elements Mn, Mg, Si and Al according to the proportion; heat the melt to 720℃~750℃, and stir evenly for 30~60 minutes; use rapid cooling technology to cast the melt into aluminum ingots with a thickness of 5~10mm, and the cooling rate is ≥50℃ / s;

[0010] S2. Hot rolling: heating the aluminum ingot to 400℃-500℃, keeping the temperature for 1-2 hours; rolling the aluminum ingot into an aluminum plate with a thickness of 1-2mm on a hot rolling mill, with a rolling speed of 1-2m / s;

[0011] S3, cold rolling: gradually cool the hot-rolled aluminum sheet to room temperature; adopt a multi-pass cold rolling process to roll the aluminum sheet to a final thickness of 5μm-10μm; the compression ratio of each pass is controlled at 10%-20%, and the cold rolling speed is 0.5-1m / s;

[0012] S4. Heat treatment: The aluminum foil after cold rolling is subjected to medium temperature annealing treatment, the annealing temperature is 200℃-300℃, and the heat preservation time is 1-2 hours; inert gas protection is used during the heat treatment process to prevent oxidation of the aluminum foil surface;

[0013] S5. Surface treatment: chemically oxidizing the surface of the annealed aluminum foil; washing the oxidized aluminum foil with deionized water and drying it with hot air at 80°C-100°C;

[0014] S6, Finished product processing: Cut the processed aluminum foil into required size and roll it into rolls; put it into storage after passing the inspection.

[0015] Furthermore, the compression ratio of each pass in the cold rolling process is gradually reduced according to the final thickness requirement, with the initial compression ratio being 15%-20% and the final compression ratio being 5%-10%.

[0016] Furthermore, the temperature of the oxidizing liquid during the surface treatment process is 20° C.-40° C., the concentration is 5%-15%, and the treatment time is 5-15 minutes.

[0017] Furthermore, the conductive coating is coated by spraying or dipping, and after coating, it is dried at 100° C.-120° C. for 10-30 minutes.

[0018] Furthermore, the oxidizing liquid in S5 is composed of 5%-10% sulfuric acid and deionized water, the treatment temperature is 20° C.-30° C., and the treatment time is 5-10 minutes.

[0019] Furthermore, argon is used as a protective gas during the S1 smelting process, and the gas flow rate is controlled at 20 to 50 L / min.

[0020] Beneficial effects:

[0021] The present invention provides an ultra-light and thin aluminum foil material for energy storage and a preparation method thereof, which has the following beneficial effects:

[0022] (1) The present invention optimizes the cold rolling and annealing processes to prepare ultra-thin aluminum foil with a thickness in the range of 5 to 10 μm while maintaining its mechanical strength and electrical conductivity, thereby significantly reducing the mass of the current collector, improving the energy density of the energy storage device, and meeting the demand for lightweight energy storage devices. By adjusting the proportion of alloy elements (Mn, Mg, Si) and optimizing the processing technology, the grain structure is effectively refined, the tensile strength and elongation of the aluminum foil are significantly improved, and high conductivity is maintained. This performance combination provides a guarantee for the stable processing and efficient current conduction of the aluminum foil.

[0023] (2) Through surface chemical oxidation treatment, the present invention forms a uniform oxide film on the surface of the aluminum foil, and the thickness of the oxide film is controlled within the range of 20 to 50 nm, which effectively improves the corrosion resistance of the aluminum foil, prolongs its service life in the energy storage device, and enhances its adhesion to the electrode active material.

[0024] (3) The present invention significantly improves the thickness uniformity and surface smoothness of the aluminum foil by optimizing the initial compression ratio of each pass in the cold rolling process to 15% to 20%, the final compression ratio to 5% to 10% and the annealing temperature to 200 to 300°C. DETAILED DESCRIPTION

[0025] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0026] Example 1: Preparation of 5 μm thick aluminum foil

[0027] Melting and casting:

[0028] Ingredients: Weigh 99.9% high-purity aluminum (98.8%), manganese (Mn) (0.5%), magnesium (Mg) (0.3%) and silicon (Si) (0.2%), and put them into a smelting furnace in proportion.

[0029] Melting: Heat the melt to 730°C and stir evenly for 60 minutes at a gas flow rate of 30 L / min under argon protection.

[0030] Casting: Rapid cooling technology is used to cast the melt into an aluminum ingot with a thickness of 7 mm, and the cooling rate is controlled at 60°C / s.

[0031] Hot rolling: heat the aluminum ingot to 450℃ and keep it warm for 1.5 hours;

[0032] The aluminum ingot is rolled into 1.5 mm thick aluminum plate on a hot rolling mill at a speed of 1.5 m / s.

[0033] Cold Rolling:

[0034] The aluminum plate is gradually cooled to room temperature;

[0035] A six-pass cold rolling process is used to gradually reduce the thickness of the aluminum sheet to 5μm;

[0036] The initial compression ratio is 18%, the final compression ratio is 8%, and the cold rolling speed is 0.8m / s.

[0037] Heat Treatment:

[0038] The cold rolled aluminum foil was placed in an annealing furnace for medium temperature annealing at 250°C for 1.5 hours;

[0039] A nitrogen protective gas flow rate of 40 L / min was used to prevent oxidation of the aluminum foil.

[0040] Surface treatment:

[0041] Oxidation liquid composition: 6% sulfuric acid and deionized water, temperature 25°C, treatment time 8 minutes;

[0042] After oxidation, the samples were rinsed with deionized water and dried with hot air at 90 °C.

[0043] Finished product processing:

[0044] Aluminum foil is cut to standard sizes and wound into rolls;

[0045] The aluminum foil is tested for thickness uniformity of ±0.5μm, tensile strength of 160MPa and conductivity of 65% IACS, and can be put into storage after passing the test.

[0046] Example 2: Preparation of 7 μm thick aluminum foil

[0047] Melting and casting:

[0048] Ingredients: Weigh 99.85% high-purity aluminum, 99.05%, manganese Mn 0.3%, magnesium Mg 0.2% and silicon Si 0.1%, and put them into a smelting furnace in proportion.

[0049] Melting: Heat the melt to 740°C and stir evenly for 45 minutes at a gas flow rate of 25L / min under argon protection;

[0050] Casting: Rapid cooling technology is used to cast the melt into an aluminum ingot with a thickness of 8 mm, and the cooling rate is controlled at 50°C / s.

[0051] Hot Rolled:

[0052] The aluminum ingot is heated to 420°C and kept warm for 2 hours;

[0053] The aluminum ingot is rolled into 1.8 mm thick aluminum plate on a hot rolling mill at a speed of 1.2 m / s.

[0054] Cold Rolling:

[0055] The aluminum plate is gradually cooled to room temperature;

[0056] An 8-pass cold rolling process is used to gradually reduce the thickness of the aluminum sheet to 7μm;

[0057] The compression ratio of the first pass is 20%, the compression ratio of the final pass is 10%, and the cold rolling speed is 0.6m / s.

[0058] Heat Treatment:

[0059] The aluminum foil is placed in an annealing furnace for medium temperature annealing at 220°C for 1 hour;

[0060] A nitrogen protective gas flow rate of 30 L / min was used to prevent oxidation of the aluminum foil.

[0061] Surface treatment:

[0062] Oxidation liquid composition: 8% sulfuric acid and deionized water, temperature 30°C, treatment time 10 minutes;

[0063] After oxidation, the samples were rinsed with deionized water and dried with hot air at 80 °C.

[0064] Finished product processing:

[0065] Aluminum foil is cut to standard sizes and wound into rolls;

[0066] The aluminum foil is tested for thickness uniformity of ±0.3μm, tensile strength of 155MPa and conductivity of 63% IACS, and can be put into storage after passing the test.

[0067] Example 3: Preparation of 10 μm thick aluminum foil

[0068] Melting and casting:

[0069] Ingredients: Weigh 99.8% high-purity aluminum 99.3%, manganese Mn 0.2%, magnesium Mg 0.1% and silicon Si 0.1%, and put them into a smelting furnace in proportion.

[0070] Melting: Heat the melt to 750°C and stir evenly for 50 minutes at a gas flow rate of 20L / min under argon protection;

[0071] Casting: Rapid cooling technology is used to cast the melt into aluminum ingots with a thickness of 10 mm, and the cooling rate is controlled at 55°C / s.

[0072] Hot Rolled:

[0073] The aluminum ingot is heated to 480°C and kept warm for 1.5 hours;

[0074] The aluminum ingot is rolled into 2mm thick aluminum plate on a hot rolling mill at a speed of 1.8m / s.

[0075] Cold Rolling:

[0076] The aluminum plate is gradually cooled to room temperature;

[0077] A 10-pass cold rolling process was used to gradually reduce the thickness of the aluminum sheet to 10 μm;

[0078] The initial compression ratio is 20%, the final compression ratio is 5%, and the cold rolling speed is 0.5m / s.

[0079] Heat Treatment:

[0080] The aluminum foil is placed in an annealing furnace for medium temperature annealing at 300°C for 2 hours;

[0081] A nitrogen protective gas flow rate of 50 L / min was used to prevent oxidation of the aluminum foil.

[0082] Surface treatment:

[0083] Oxidation liquid composition: 10% sulfuric acid and deionized water, temperature 28°C, treatment time 12 minutes;

[0084] After oxidation, the samples were rinsed with deionized water and dried with hot air at 100 °C.

[0085] Finished product processing:

[0086] Aluminum foil is cut to standard sizes and wound into rolls;

[0087] The aluminum foil is tested for thickness uniformity of ±0.2μm, tensile strength of 150MPa and conductivity of 60% IACS, and qualified ones are put into storage.

[0088] As a further improvement, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An ultra-light and thin aluminum foil material for energy storage, characterized in that: The alloy components of the aluminum foil material include Al, Mn 0.2% to 0.5%, Mg 0.1 to 0.3%, and Si 0.1 to 0.2%. The thickness of the aluminum foil is 5 to 10 μm. The surface of the aluminum foil is coated with an oxide film, and the thickness of the oxide film is 20 to 50 nm.

2. The method for preparing an ultra-light and thin aluminum foil material for energy storage according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Melting and casting: Put high-purity aluminum and trace alloy elements into a melting furnace according to the proportion, and add alloy elements Mn, Mg, Si and Al according to the proportion; heat the melt to 720℃~750℃, and stir evenly for 30~60 minutes; use rapid cooling technology to cast the melt into aluminum ingots with a thickness of 5~10mm, and the cooling rate is ≥50℃ / s; S2. Hot rolling: heating the aluminum ingot to 400℃-500℃, keeping the temperature for 1-2 hours; rolling the aluminum ingot into an aluminum plate with a thickness of 1-2mm on a hot rolling mill, with a rolling speed of 1-2m / s; S3, cold rolling: gradually cool the hot-rolled aluminum sheet to room temperature; adopt a multi-pass cold rolling process to roll the aluminum sheet to a final thickness of 5μm-10μm; the compression ratio of each pass is controlled at 10%-20%, and the cold rolling speed is 0.5-1m / s; S4. Heat treatment: The aluminum foil after cold rolling is subjected to medium temperature annealing treatment, the annealing temperature is 200℃-300℃, and the heat preservation time is 1-2 hours; inert gas protection is used during the heat treatment process to prevent oxidation of the aluminum foil surface; S5. Surface treatment: chemically oxidizing the surface of the annealed aluminum foil; washing the oxidized aluminum foil with deionized water and drying it with hot air at 80°C-100°C; S6, Finished product processing: Cut the processed aluminum foil into required size and roll it into rolls; put it into storage after passing the inspection.

3. The method for preparing an ultra-light and thin aluminum foil material for energy storage according to claim 1, characterized in that: The compression ratio of each pass in the cold rolling process is gradually reduced according to the final thickness requirement, the initial compression ratio is 15%-20%, and the compression ratio of the last pass is 5%-10%.

4. The method for preparing an ultra-light and thin aluminum foil material for energy storage according to claim 1, characterized in that: The temperature of the oxidizing liquid during the surface treatment process is 20° C.-40° C., the concentration is 5%-15%, and the treatment time is 5-15 minutes.

5. The method for preparing an ultra-light and thin aluminum foil material for energy storage according to claim 1, characterized in that: The conductive coating is coated by spraying or dipping, and after coating, it is dried at 100° C.-120° C. for 10-30 minutes.

6. The method for preparing an ultra-light and thin aluminum foil material for energy storage according to claim 1, characterized in that: The oxidation liquid in S5 is composed of 5%-10% sulfuric acid and deionized water, the treatment temperature is 20°C-30°C, and the treatment time is 5-10 minutes.

7. The method for preparing an ultra-light and thin aluminum foil material for energy storage according to claim 1, characterized in that: During the S1 smelting process, argon was used as the protective gas, and the gas flow rate was controlled at 20-50 L / min.

Citation Information

Cited By

  • Ultrathin high-performance battery aluminum foil material and preparation method thereof

    CN120662815A